Insecticidal and genotoxic potential of two semi-synthetic derivatives of dillapiole for the control of Aedes (Stegomyia) aegypti (Diptera: Culicidae) - Domingos, Pedro Rauel Cândido; Pinto, Ana Cristina da Silva; Santos, Joselita Maria Mendes dos; Rafael, Míriam Silva (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2014)
The effects of two semi-synthetic dillapiole derivatives, ethyl-ether dillapiole and n-butyl ether dillapiole, on eggs and larvae of Aedes aegypti were studied in view of the need for expansion and renovation of strategic action to control this mosquito - the vector of Dengue virus -, which currently shows a high resistance to chemical insecticides. Eggs and third-instar larvae of A. aegypti that had been exposed to different concentrations of these two compounds showed toxicity and susceptibility, with 100% mortality. Classical cytogenetic assays showed genotoxicity caused by the two compounds in A. aegypti from the cumulative effect of nuclear abnormalities, indicating that these derivatives may be potential alternatives to control A. aegypti. © 2014.
Keywords: Dill Apiole; Dill Apiole Derivative; Larvicidal Agent; Unclassified Drug; 1,3 Dioxolane Derivative; 5-allyl 6,7-dimethoxy 1,3-benzodioxole; Allyl Compound; Insecticide; Adult; Aedes Aegypti; Cell Division; Controlled Study; Cytotoxicity; Egg Laying; Female; Genotoxicity; Insecticidal Activity; Interphase; Larva; Lc50; Neuroblast; Nonhuman; Oocyte; Priority Journal; Vector Control; Aedes; Animals; Chemistry; Dengue Virus; Disease Carrier; Dna Damage; Metabolism; Synthesis; Virology; Aedes; Allyl Compounds; Animal; Dengue Virus; Dioxoles; Dna Damage; Insect Vectors; Insecticides